2008
DOI: 10.1074/jbc.m804353200
|View full text |Cite
|
Sign up to set email alerts
|

High Affinity Interaction between a Bivalve C-type Lectin and a Biantennary Complex-type N-Glycan Revealed by Crystallography and Microcalorimetry

Abstract: Codakine is an abundant 14-kDa mannose-binding C-type lectin isolated from the gills of the sea bivalve Codakia orbicularis. Binding studies using inhibition of hemagglutination indicated specificity for mannose and fucose monosaccharides. Further experiments using a glycan array demonstrated, however, a very fine specificity for N-linked biantennary complex-type glycans. An unusually high affinity was measured by titration microcalorimetry performed with a biantennary Asn-linked nonasaccharide. The crystal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 53 publications
(36 reference statements)
0
31
0
1
Order By: Relevance
“…S7, clearly showing that citric acid inhibits glycolipid binding to Mincle, whereas acetic acid does not. Notably, another mannose-binding C-type lectin, codakine, bound similar positions of oxygens of glycerol and glycan in a Ca 2+ ion-mediated manner (26). Citric acid is likely accommodated at this position to block the ligands, and hydroxyl groups are likely used following the coordination of Ca 2+ ions generally observed in CLRs.…”
Section: Discussionmentioning
confidence: 96%
“…S7, clearly showing that citric acid inhibits glycolipid binding to Mincle, whereas acetic acid does not. Notably, another mannose-binding C-type lectin, codakine, bound similar positions of oxygens of glycerol and glycan in a Ca 2+ ion-mediated manner (26). Citric acid is likely accommodated at this position to block the ligands, and hydroxyl groups are likely used following the coordination of Ca 2+ ions generally observed in CLRs.…”
Section: Discussionmentioning
confidence: 96%
“…The first Glc and the branching Gal residues of the outer core bind via Arg H52 and Asn H53, which explains the enhanced affinity observed for oligosaccharides containing an outer core and a branching substitution at position 6 of the first hexose (30). These residues are bound independently of their stereochemistry of ring hydroxyls, which opens the possibility for WN1 222-5 recognition of LPS with other outer core types.…”
mentioning
confidence: 98%
“…Remarkably, WN1 222-5 binds its LPS core epitope even in the presence of O-PS. By using whole LPS and a number of neoglycoconjugates containing core-OS from all E. coli core types, S. enterica, and the mutant strain E. coli J-5 in ELISA binding studies, we previously identified parts of an inner core epitope accessible to high-affinity binding of mAb WN1 222-5 (27), with an affinity orders of magnitude higher than that determined for mAb Se155-4 against Salmonella group B O-PS and most other carbohydrate binding proteins (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A, the four carbohydrate-binding sites of the CEL-IV tetramer are oriented apart from one another. Because (23). Although the fold of the CEL-IV protomer resembles the other C-type CRDs, as representatively shown for C. echinata lectin CEL-I (6), tunicate (Polyandrocarpa misakiensis) lectin TC14 (11), and rat mannose-binding lectin MBL (MBP-A) (24) (Fig.…”
Section: Crystallization and Structure Determination Of Cel-iv-mentioning
confidence: 77%